2012
DOI: 10.1530/joe-12-0278
|View full text |Cite
|
Sign up to set email alerts
|

The role of adipokines in β-cell failure of type 2 diabetes

Abstract: Abstractb-Cell failure coupled with insulin resistance is a key factor in the development of type 2 diabetes. Changes in circulating levels of adipokines, factors released from adipose tissue, form a significant link between excessive adiposity in obesity and both aforementioned factors. In this review, we consider the published evidence for the role of individual adipokines on the function, proliferation, death and failure of b-cells, focusing on those reported to have the most significant effects (leptin, ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
141
2
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(158 citation statements)
references
References 73 publications
4
141
2
11
Order By: Relevance
“…The lipid profile obtained in this study showed a significant decrease in the triglyceride level and an increase in the high density lipoprotein cholesterol of the tomatoes treated groups when compared with the hypertensive untreated group. Lipidemia observed in the hypertensive untreated group may be as a result of an increase in visceral adipose mass (Brown and Dunmore, 2013) or may be due to a low activity of cholesterol biosynthesis enzymes (Tanko et al, 2016). Though anabolic steroids may increase blood pressure due to the sodium retention property, high dose of steroids use inhibits the enzyme 11-beta hydroxylase which leads to excessive production of deoxycortisterone, a mineralocorticoids in the adrenal glands and in due course a water and sodium retention.…”
Section: Resultsmentioning
confidence: 99%
“…The lipid profile obtained in this study showed a significant decrease in the triglyceride level and an increase in the high density lipoprotein cholesterol of the tomatoes treated groups when compared with the hypertensive untreated group. Lipidemia observed in the hypertensive untreated group may be as a result of an increase in visceral adipose mass (Brown and Dunmore, 2013) or may be due to a low activity of cholesterol biosynthesis enzymes (Tanko et al, 2016). Though anabolic steroids may increase blood pressure due to the sodium retention property, high dose of steroids use inhibits the enzyme 11-beta hydroxylase which leads to excessive production of deoxycortisterone, a mineralocorticoids in the adrenal glands and in due course a water and sodium retention.…”
Section: Resultsmentioning
confidence: 99%
“…Загалом панкреатична екзокринна не-достатність підшлункової залози спостерігається при-близно в однієї третини пацієнтів, які страждають від ожиріння [58].…”
Section: патогенетичні аспекти екзокринної недостатності підшлунковоїunclassified
“…Протизапальні ефекти адипонек-тину включають зниження регуляції прозапальних цитокінів і підвищення регуляції протизапальних ци-токінів, зокрема зниження секреції моноцитами ІЛ-6 і ФНП-α. Прозапальна активність лептину проявля-ється його здатністю вивільняти ІЛ-6 і ФНП-α з ма-крофагів [58,61].…”
Section: роль адипоцитокінів у розвитку зовнішньосекреторної та внутрunclassified
“…This group of molecules possesses a myriad of effects on diverse tissue/organs, including but not limited to the control of inflammation, fat distribution, insulin sensitivity and secretion, energy balance, appetite and satiety [39][40][41][42]. Some of the best studied and relevant adipokines in obesity and type 2 DM are leptin, adiponectin, TNF-α, IL-6, IL-1, resistin, dipeptidyl peptidase IV, apelin, monocyte chemotactic protein-1 (MCP-1), and so on [40,41]. Interestingly, adipokines can act as either pro-inflammatory or anti-inflammatory signaling molecules.…”
Section: Cytokines and Adipokines In Obesity And Type 2 Dmmentioning
confidence: 99%